2001
DOI: 10.1054/bjoc.2001.2074
|View full text |Cite
|
Sign up to set email alerts
|

Identification of human renal cell carcinoma associated genes by suppression subtractive hybridization

Abstract: Renal cell carcinoma (RCC) accounts for approximately 3% of adult malignancies and 1.4% of cancer-related deaths (Reis and Faria, 1994). The prognosis of RCC remains poor. One third of the patients already have metastases when first consulting the hospital. Another 30-40% of patients develop metastases after surgical excision of the primary tumour (Ravaud and Debled, 1999). RCC are radioresistant (Nieder et al, 1996) and more than 80% are chemoresistant (Mickisch, 1994). Since RCC are presumed to be immunogeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
83
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(88 citation statements)
references
References 75 publications
5
83
0
Order By: Relevance
“…Nevertheless, the renal cell lines stand out as consistently maintaining CCND1 expression under hypoxia in contrast to all other types examined here and reported in the literature. Our findings are in agreement with clinical data that approximately 75% of RCCs expressed a higher level of CCND1 protein than the normal kidney cortex (Lin et al, 1998;Aaltomaa et al, 1999;Hedberg et al, 1999;Stassar et al, 2001).…”
Section: Discussionsupporting
confidence: 93%
“…Nevertheless, the renal cell lines stand out as consistently maintaining CCND1 expression under hypoxia in contrast to all other types examined here and reported in the literature. Our findings are in agreement with clinical data that approximately 75% of RCCs expressed a higher level of CCND1 protein than the normal kidney cortex (Lin et al, 1998;Aaltomaa et al, 1999;Hedberg et al, 1999;Stassar et al, 2001).…”
Section: Discussionsupporting
confidence: 93%
“…Several studies have shown that overexpression of LOX was significantly associated with poorly differentiated, high grade tumors, increased recurrence rates and decreased overall survival (Stassar et al, 2001;Lapointe et al, 2004;Albinger-Hegyi et al, 2010). Similar results were observed in our study, we found that the expression of LOX was significantly higher in NSCLC tumor tissues than paired normal tissue.…”
Section: Discussionsupporting
confidence: 91%
“…ATX stimulates both cell proliferation and cell motility of cancer cells through LPA production (5). In addition, overexpression of ATX is frequently associated with malignant tumors such as small cell lung cancer (26), renal cell cancer (27), hepatocellular carcinoma (28,29), breast cancer (30,31), Hodgkin lymphoma (32), thyroid cancer (33), and glioblastoma (17). Thus, ATX has been implicated in the progression of malignant tumors.…”
Section: Discussionmentioning
confidence: 99%